Investigation of the performance of basalt fiber reinforced Cement-Stabilized macadam derived from moderately weathered tunnel slag - Chao Zhao; Ding Wang; Yantao Zheng; Hongbo Zhang; Changwu Liu (Scientific Reports)
Abstract This study aims to promote the effective utilization of moderately weathered tunnel slag, preserve the ecological integrity of construction sites, and support sustainable development. An orthogonal experimental design was used to examine the effects of aggregate gradation, cement content, and curing age on the uniaxial compressive strength (UCS) of Cement-Stabilized Macadam (CSM) containing tunnel slag. Range analysis showed that CSM made with moderately weathered slag exhibits favorable mechanical properties. The optimal condition combination was Gradation C, 6% cement, and a curing age of 28 days. Analysis of variance (ANOVA) indicated that cement content and curing age significantly influenced UCS, with cement content having the greatest effect, followed by curing age. Gradation showed no statistically significant effect. Based on these findings, a series of UCS tests, indirect tensile strength (ITS) tests, and freeze-thaw tests were conducted to evaluate the impact of basalt fiber (0.07% by mass, 12 mm in length) reinforcement on the mechanical properties and frost resistance of CSM. The addition of basalt fibers slightly reduced UCS, from 7.08 MPa to 6.97 MPa, but significantly increased ITS, from 0.337 MPa to 0.374 MPa. Frost resistance also improved significantly. Post-freeze–thaw mass loss decreased from 0.121 to 0.095%, and residual compressive strength increased from 88.28 to 96.99%. Compared to existing studies, this research takes an initial step in exploring the reuse of moderately weathered tunnel slag and the synergistic effects of fiber reinforcement and slag on CSM performance. The findings contribute to cost-effective infrastructure development and provide notable ecological benefits, offering a useful reference for future engineering applications.